2015
DOI: 10.1039/c5ja00127g
|View full text |Cite
|
Sign up to set email alerts
|

Shading in TXRF: calculations and experimental validation using a color X-ray camera

Abstract: Absorption effects in total reflection X-ray fluorescence (TXRF) analysis are important to consider, especially if external calibration is to be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…However, these techniques require the preparation of special equipment such as a pico-droplet inkjet printer or nano-droplet dispensing device to obtain nano-pico droplets. A strong shading effect for normal residue made from µL droplets in TXRF has been reported by a study using a color X-ray camera (CXC) [6]. 2D distribution of XRF signals from nano droplets was obtained by the CXC under total reflection conditions.…”
Section: Introductionmentioning
confidence: 90%
“…However, these techniques require the preparation of special equipment such as a pico-droplet inkjet printer or nano-droplet dispensing device to obtain nano-pico droplets. A strong shading effect for normal residue made from µL droplets in TXRF has been reported by a study using a color X-ray camera (CXC) [6]. 2D distribution of XRF signals from nano droplets was obtained by the CXC under total reflection conditions.…”
Section: Introductionmentioning
confidence: 90%
“…Later a 2 μL of a droplet of Ga at 5 μg/mL was added directly over to the sample holder. The very-small volumes of the droplets were chosen in order to reduce effects over the morphology of the sample [35] and effects over the excitation source [36]. We replicated the methodology previously applied for Cobalt evaluation in injectable multivitamins [37], obtaining in this case uncertainties in the order of 10%.…”
Section: Sample Preparationmentioning
confidence: 99%
“…A re-drying process can cause recrystallization processes which mainly occur at places already enriched in this specific element, causing a non-uniformity across the sample affecting the accuracy of a quantitative analysis. The evaporation behavior of different kinds of droplets and studies on their morphology and homogeneity once dried have been studied and reported elsewhere [7,[39][40][41]. In TXRF, the superposition or interference between the incoming and reflected beams at small grazing incidence angles can cause X-ray standing waves above and below the substrates.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%